Phonetic accompaniment and its semantic reflections on the Holy Qur’an: A computational phonological study - Ahmed Mahmoud, Ahmed Ragheb (2009)
The research highlights the interactive relationship between Speech and Symantec according to the output of computational linguistics, trying to monitor the relations of statistical research between context of phonology and meaningful results of that speech. The research also tries to highlight this relationship through a systematic analysis of the Arabic short-and long- movements, and how to determine the extent of time via computer, then monitoring the phonological effects that lead to an increase/decrease of this range, then devise dimensions results of these movements. The research will then discuss the allophone of qalqalah and its meaning values in the Qur'an.